Humboldt and the modern German university An intellectual history - Östling, Johan (Lund University Press, 2018)
This book is about the idea of the university in modern Germany. Its primary focus is how the transformation of the Humboldtian tradition gave direction to debates around higher education. By combining approaches from intellectual history, conceptual history and the history of knowledge, the study investigates the ways in which Humboldt's ideas have been appropriated for various purposes in different historical contexts and epochs. Ultimately, it shows that Humboldt's ideals are not timeless - they are historical phenomena and have always been determined by the predicaments and issues of the day. Nevertheless, many of the key concepts and fundamental ideas have endured throughout the twentieth century, though they have been interpreted in different ways.